A Gap Analysis of Mental Health and Addictions Support Services in Richmond, British Columbia — A Community-Based Research Study - Chopra, Shelly (The Meducator, 2013)
Across Canada, mental health and addictions (MHA) has become an area of concern for health providers: it is estimated that one in five adults is affected by a mental illness or addiction. In line with the provincial Ministries of Health Services and Child and Family Development ten-year plan to address MHA in BC, a community-based MHA service gap analysis was undertaken in the present study in Richmond, BC. The primary objectives of this research project were to identify and validate gaps in MHA support services in Richmond based on the informed perspectives of MHA community service providers. In addition to independent and consumer informants, a total of 22 administrators and frontline workers from 10 Richmond-based organizations were interviewed for the purposes of gap validation. Analysis of key informant responses for recurring themes elucidated four main areas of improvement: navigation of MHA services, continuum of support, personalized support, and outreach. Following a meeting among key informants to discuss the results of the current gap analysis, the expectation was raised of developing a strategic action plan to address gaps in MHA service in Richmond, BC.